Level structure of 80Rb studied with the 79Br(α, 3n) reaction - Behar, M.; Filevich, A.; García Bermúdez, G.; Mariscotti, M. A .J. (Elsevier B.V., 1977)
Fil: Behar, M. Comisión Nacional de Energía Atómica; Argentina